PENCATATAN KEUANGAN DAN PENYUSUNAN LAPORAN KEUANGAN UMKM (Universitas Wijayakusuma Purwokerto, 2023)
Accounting practice is a solution for SMEs. MSMEs need to prepare financial reports in accordance with the regulations listed in the Regulation of the Minister of Cooperatives and Small and Medium Enterprises. The importance of applying accounting knowledge in managing the finances of Micro, Small and Medium Enterprises (MSMEs) is considered to be poorly understood by actors. There are still many business actors who have not recorded their business financial statements properly, in fact, some have not kept records. Small and medium entrepreneurs usually only do bookkeeping to the extent of recording income and expenses. Because accounting has a big influence on the success of business actors. Chronologically, the order in the accounting cycle goes through several stages, such as the recording stage, the summary stage, and the financial report preparation stage. This community service activity aims to increase knowledge and ability to record and prepare financial reports for MSMEs in Maruyung Village, Padaherang District, Pangandaran Regency.